HUBUNGAN ANTARA POLA SEKSUALITAS GRAVIDA DENGAN KETUBAN PECAH DINI (Jurnal Medika : Karya Ilmiah Kesehatan, 2018)
The rate of maternal mortality in Indonesia is still the highest in ASEAN which is 359 / 100,000 live births with premature rupture of membranes in Indonesia around 114 cases from all labor and maternal mortality due to premature rupture of membrane about 15 cases from all normal deliveries. This study aims to analyze the correlation between of gravida sexual pattern with premature rupture of membranes in Paradise Hospital Kecamatan Simpang Empat Kabupaten Tanah Bumbu.The method in this study was an analytical survey with cross sectional design. Sample were 46 pregnant women conducted by accidental sampling technique, and analyzed by Chi Square test.The results of the study obtained almost all (75.0%) of respondents who perform sexual patterns experience premature rupture of membranes. Statistical test obtained value p = 0,008 (